Introductory mycology - Alexopoulos, Constantine John, 1907-1986 (Wiley, 1979)
Revised and updated in accordance with modern taxonomic proposals, this edition offers a well-documented, logical and clear explanation of the structure and classification of fungi along with an introduction to physiological, biochemical, genetic and ecological data. The taxonomic approach provides a framework with predictive value. Therefore, the discussions of the numerous activities of fungi that directly or indirectly impact other living things, including humans, are discussed in the context of their close relatives. Contains scores of illustrations, life cycle drawings, tables and new photographs.